Stravinsky and U2 Fix Psalm 40 - Lewis, Andrew Zack (Journal of the bible and its reception, 2015)
This paper examines the reception of Psalm 40 by Igor Stravinsky in the second movement of his “Symphony of Psalms” and by U2 in their song “40,” the final track on their 1983 album War. Though both limit their reception to only the first three verses of the psalm, their appropriation of the text indicates two different interpretations of the psalm within the Canon. Stravinsky places the verses between the concluding verses of Psalm 39 and the entirety of Psalm 150, the result of which is a typical personal lament psalm made up of lament, petition, assurance, and praise—a very different structure than the canonical Psalm 40's assurance followed by lament. U2's appropriation, on the other hand, is arguably more faithful to the text of the canonical Psalm 40 in that its concluding lyrics hearken back to the harrowing opening track of their album, the “lament” “Sunday Bloody Sunday.” The paper concludes by arguing that both Stravinsky and U2 remain faithful to the spirit of the psalter as a whole by re-appropriating the words of the psalmist for each musician's own Sitz I’m Leben.